2013
DOI: 10.1056/nejmoa1300610
|View full text |Cite
|
Sign up to set email alerts
|

Nonemergency PCI at Hospitals with or without On-Site Cardiac Surgery

Abstract: Nonemergency PCI procedures performed at hospitals in Massachusetts without on-site surgical services were noninferior to procedures performed at hospitals with on-site surgical services with respect to the 30-day and 1-year rates of clinical events. (Funded by the participating hospitals without on-site cardiac surgery; MASS COM ClinicalTrials.gov number, NCT01116882.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 24 publications
6
43
0
1
Order By: Relevance
“…Since 2006, 11 original studies and 3 meta-analyses on the topic of PCI without on-site surgery have been identified by a computerized systematic literature search using Medline (PubMed and Ovid) and Cochrane Databases [9,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…Since 2006, 11 original studies and 3 meta-analyses on the topic of PCI without on-site surgery have been identified by a computerized systematic literature search using Medline (PubMed and Ovid) and Cochrane Databases [9,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
“…The 9-month rates of major adverse cardiac events were 11.2% and 12.1% at hospitals with and without on-site surgery, respectively (P ¼ 0.05 for noninferiority). A similar, but smaller randomized study of nonemergency PCI was performed in Massachusetts hospitals [11]. The rates of major adverse cardiac events were 9.5% in hospitals without on-site cardiac surgery and 9.4% in hospitals with on-site cardiac surgery at 30 days (relative risk, 1.00; 95% one-sided upper confidence limit, 1.22; P < 0.001 for noninferiority) and 17.3% and 17.8%, respectively, at 12 months (relative risk, 0.98; 95% one-sided upper confidence limit, 1.13; P < 0.001 for noninferiority).…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, this proliferation has been aided, in part, by data suggesting that PCI can be performed safely without on-site cardiac surgery. 9,10 Given the aforementioned association between PCI volume and outcomes, the net effect of any such growth is likely to represent a complex balance between improved access and decreasing procedural volumes (both for hospitals and operators).…”
Section: Circulationmentioning
confidence: 99%